Pengaruh Penambahan Bunga Telang (Clitoria ternatea) terhadap pH, Total Bakteri Asam Laktat, Total Yeast, dan Antibakteri Masker Kefir - Setiawan, Raudya Arini; Wulandari, Eka; Pratama, Andry (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Kefir is the result of milk fermentation with microorganisms in kefir grains consisting of lactic acid bacteria and yeast. Processing kefir into facial care products such as masks is one of the innovations that can be done to increase the value of kefir. Butterfly pea (Clitoria ternatea) is an herbal plant that has many benefits derived from the nutrients it contains. This study aims to determine the effect of adding butterfly pea extract on the pH, total lactic acid bacteria, total yeast, and antibacterial activity in kefir masks. This research was conducted experimentally using a Completely Randomized Design (CRD) with 5 concentration treatments (P1=0.1%, P2=0.3%, P3=0.5%, P4=0.7%, P5=0.9%) and repeated 4 times. The research data obtained were processed using analysis of variance and Duncan's multiple range test. The results showed that the addition of telang flower extract can increase the total lactic acid bacteria, total yeast and antibacterial activity of kefir masks. However, it has the same effect on the pH value of kefir mask. The addition of 0,9% butterfly pea extract in kefir mask resulted in total lactic acid bacteria of 1.26×109 cfu/ml, total yeast of 2.21×109cfu/ml, the highest antibacterial activity of 8.23 mm and pH of 4.14.